PENYULUHAN DAMPAK LIMBAH BAHAN PLASTIK DAN PEMANFAATANNYA SEBAGAI USAHA PENGENDALIAN PENCEMARAN LINGKUNGAN - Puguh Sujarta (JURNAL PENGABDIAN PAPUA, 2017)
Environmental pollution occurs because of lack of knowledge of the environment of the community. Habit of throwing plastic garbage cans to make an impact for human life. The plastic waste is not easily degraded by decomposing animals. The amount of plastic waste can be hazardous to the environment and public health. Therefore, the need of public awareness of plastic waste is not his to control environmental pollution. The purpose of the implementation of the service activity is shown to explain to the concerns about the dangers of plastic waste to health and the environment; The second is to make some crafts of plastic waste materials. Activities that do on Saturday, October 15th, 2016 at SMP Depapre, Jayapura. The audience is 40 students. Using speech and simulation methods. The results showed that the activities of participants in the activities with enthusiastic and understand about the hazard of plastic waste. Keywords: plastic waste, impact, polluiton, environment